What determines the innovation capability of firm founders? - Spyros Arvanitis; Tobias Stucki (ETH Zurich, KOF Swiss Economic Institute, 2010)
Innovative start-ups, not start-ups in general, seem to be important drivers of economic growth. However, little is known about how such firms look like. As activities of start-ups are strongly related to firm founders, we investigate this question focusing on the innovation capability of firm founders. We find that the combination of different founder characteristics such as university education (at best a combination of technical and commercial education), prior experience in R&D, and strong motivation to realize own innovative ideas increases innovative activities of start-ups by more than 40%.
Keywords: M13; L26; O30; 330; start-ups; innovation; founder characteristics; Unternehmensgründung; Innovation; Qualifikation; Unternehmer; Schweiz